PP.02.20: WORLD HEALTH ORGANIZATION CARDIOVASCULAR RISK STRATIFICATION AS A MARKER OF HYPERTENSIVE TARGET ORGAN DAMAGE. (June 2015) - Piskorz, D.; Tommasi, A.
Abstract : Objective: The aim of the present study is to determine if cardiovascular risk (CVR) stratification of WHO Americas B is a marker of target organ damage (TOD) in hypertensive patients. Design and method: Hypertensive non treated consecutive patients (p) assisted at first visit in a specialized center were included. CVR was stratified according to WHO Americas B area table. Left ventricular mass index (LVMI) and tissue Doppler diastolic and systolic function was measured as Lang RM et al JASE 2005 and Nagueh SF et al JASE 2009. Cardiac TOD was considered according to 2013 ESH/ESC Guidelines J Hypertension 2013. Glomerular filtration rate was calculated by MDRD formula, a value < 60 ml/min/1, 73m2 was considered TOD. Systolic aortic pressured (CAoP) was measured by radial tonometry and classified as McEniery CM et al Hypertension 2008. Continue variables are reported as means with standard deviation and discrete variables as absolute values and percentages. Statistical analysis was performed with ANOVA test, significant differences were considered with a p value < 0.05. Results: 292 p were included; 159 p (54.5%) had CVR < 10 %, 90 p (30.8%) CVR 10%-20 % and 43 p (14.7%) CVR > 20 %. Sample mean age was 58.5+-12.7 years; 151 p (51.7 %) were males. Type 2 Diabetes had 21 p (7.2%), dyslipidemia 94 p (32.2%), and smokers were 44 p (55.1%). The table shows data of TOD. (See table on the following page) Figure. No caption available. Conclusions: 1) LVMI increases and diastolic and systolic function are more frequently altered as CVR increases; 2) GFR < 60 ml/min/1, 73m2 is more frequent as CVR increases; 3) although mean CAoP in higher CVR patients, the frequency of abnormal CAoP is higher in low CVR patients.